2023
DOI: 10.3390/ijms24021689
|View full text |Cite
|
Sign up to set email alerts
|

CLC-Pred 2.0: A Freely Available Web Application for In Silico Prediction of Human Cell Line Cytotoxicity and Molecular Mechanisms of Action for Druglike Compounds

Abstract: In vitro cell-line cytotoxicity is widely used in the experimental studies of potential antineoplastic agents and evaluation of safety in drug discovery. In silico estimation of cytotoxicity against hundreds of tumor cell lines and dozens of normal cell lines considerably reduces the time and costs of drug development and the assessment of new pharmaceutical agent perspectives. In 2018, we developed the first freely available web application (CLC-Pred) for the qualitative prediction of cytotoxicity against 278… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…We found that all ACE-Is could actually be active against the variety of ovarian cancer cells. The responsive models identified in our simulation included: A2780cisR (cisplatin-resistant ovarian carcinoma), A2780S (ovarian endometrioid adenocarcinoma), SK-OV3, OVCAR-3, OVCAR-4, OVCAR-5, OVCAR-8, IGROV1, NCI/ADR-RES and PA-1 at GI 50 threshold of 1nM and 10 nM [ 23 ]. The compounds with the highest probability of being cytotoxic were demonstrated in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that all ACE-Is could actually be active against the variety of ovarian cancer cells. The responsive models identified in our simulation included: A2780cisR (cisplatin-resistant ovarian carcinoma), A2780S (ovarian endometrioid adenocarcinoma), SK-OV3, OVCAR-3, OVCAR-4, OVCAR-5, OVCAR-8, IGROV1, NCI/ADR-RES and PA-1 at GI 50 threshold of 1nM and 10 nM [ 23 ]. The compounds with the highest probability of being cytotoxic were demonstrated in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The output yielded P a and P i values for each cell line, which corresponded to “probability of being active” and “probability of being inactive”, respectively. If the inequality P a > P i was fulfilled, the compound was considered more likely to belong to the subclass of active compounds than inactive ones, based on the similarity of chemical structure [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…A large number of compound-centric biological databases have been established in the past decades [27][28][29] . These databases have served various purposes in drug discovery, from identifying the bioactivity of unknown compounds 30,31 to the prediction of mechanisms of action 32,33 , or simply for the virtual screening of drug candidates 34,35 . While previous research by Joerg Ohms (2022) explored the coverage of patent documents in relation to chemicals in two patent databases (SureChEMBL and Patentscope), the scope of this study was limited to manually comparing a set of chemicals between PubChem Substance and patent compounds 36 .…”
Section: Pubchem Demonstrates Highest Coverage Of Patent Compoundsmentioning
confidence: 99%
“…A large number of compounds-centric biology databases have been established in the past decades [38][39][40][41]. These databases have served various purposes in drug discovery, from identifying the bioactivity of unknown compounds [42,43] to the prediction of mechanism-of-action (MoA) [44,45] or simply for the virtual screening of drug candidates [46,47]. While previous research by Joerg Ohms (2021) explored the coverage of patent documents in relation to chemicals across patent databases, the author was restricted to comparing the compound coverage between PubChem and patent compounds [48].…”
Section: Cross-resource Comparison Of Compounds In Patentsmentioning
confidence: 99%